FUNGSI TENAGA KESEJAHTERAAN SOSIAL DI KECAMATAN POASIA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Badaruddin, Muhammad Ali; Hos, Jamaluddin; Tanzil, Tanzil (WELL-BEING: Journal of Social Welfare, 2021)
This research was conducted in Poasia District, Kendari City. The objectives of this study were (1) To determine the role of social welfare workers in Poasia District, Kendari City (2) To determine the driving and inhibiting factors of the role of social welfare workers in Poasia District, Kendari City. The research method used is using qualitative research methods, qualitative methods are research methods that produce descriptive data and written or spoken words from people's behavior can be observed, the research technique used is observation / observation, namely the researcher goes directly to the field to obtain data and prepare the tools and materials used at the time of the research. Interviews were conducted to gather information such as the role of social welfare workers and the driving and inhibiting factors in Poasia District, Kendari City. Documentation is done in order to strengthen the data from the results of the interviews conducted in the observation. The technique of determining informants in this research was carried out by purposive sampling. Data were analyzed using data reduction techniques, data presentation, and drawing conclusions. The results of this study indicate that in Poasia District there are still many underprivileged people, then the government provides assistance through the Ministry of Social Affairs for less fortunate families. This assistance is provided through a different home program. This program aims to improve the quality of housing for underprivileged people.